A Piece of Inclusive Democracy in Indonesia: The Case of Minahasan Society’s Acceptance of the Muslim Community - Kaunang, Rolina Anggereany Ester; Nelwan, Gerry; Tumiwa, Krueger Kristanto (Religió Jurnal Studi Agama-agama, 2025)
Contemporary democracy often faces challenges in realizing inclusivity, particularly regarding minority groups’ access to the right to speak, participate, and make collective decisions. In this respect, this article examines inclusive democratic practices based on local values inherited from Minahasan ancestors, highlighting symbols and practices centered on the Watu Pinawetengan site. This research focuses on the Minahasan community’s acceptance of the Muslim immigrant community as a minority group that was vulnerable to being marginalized. Using descriptive qualitative methods and analysis based on Marianne Moyaert’s hospitality perspective, this article examines textual sources such as journal articles, books, and other relevant documents to understand how hospitality values are embedded in Minahasan social practices. The results show that deliberative practices at Watu Pinawetengan, where Minahasan ancestors divided territory dialogically and equally, symbolize a legacy of participatory and open democracy. These values continue to be lived out in inter-community relationships, including interactions with Muslims exiled to the region during the colonial period. This article argues that democracy can be constructed not only through formal institutions but also through the reinterpretation of local cultural heritage that upholds openness, equality, and hospitality across identities.